THE EFFECT OF pH CONDITIONS ON PHYSIOLOGICAL RESPONSE OF SEAGRASS LEAVES Cymodocea rotundata (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Increased carbon dioxide (CO2) in the atmosphere causes ocean acidification. Acidification becomes a threat to seagrass. Nowadays, one of the challenges that must be faced is to predict the long-term impact of acidification on the physiology of seagrass. This research aims to analyze seagrass Cymodocea rotundata leave physiology responses to pH that consists of chlorophyll-a and b content, photosynthesis rate, and growth rate of seagrass leaf. This research was conducted on September – December 2017 in Marine Habitat Laboratory, Department of Marine Science and Technology, Bogor Agricultural University. The method used a completed randomized design with five repetitions. pH treatment used in this research is low pH (7.55), medium pH (7.78), and control (8.20). The setting of pH value was done by adding CO32-. Chlorophyll-a and b contents, photosynthesis rate, and growth rate on C. rotundata leaf are higher on control pH treatment than medium pH (7.78) and low pH (7.55). ANOVA test shows that only chlorophyll-a is significantly different. The difference pH affects the chlorophyll content of a and b, photosynthesis rate, and leaf growth rate. The low pH of seawater has been shown to inhibit the physiological activity of C. rotundata leaves.